O profissional da informação em atividades de inteligência competitiva - Ester Laodiceia Santos (2009)
The role of information professionals librarians, archivists, Master and PhD level Information Science academics in competitive intelligence activities in public and private institutions has been analyzed. The professional categories considered as information professionals with regard to profile, skills and abilities have been presented and a briefdescription of information professionals according to the classification proposed by Mueller (2004) has been made. The evolution of competitive intelligence as an activity, the professionals skills and expertise as well as his or her role in multidisciplinary competitive intelligence teams have been presented. Competitive intelligence as an activity has beenanalyzed in such a way to highlight its interface with Information Science, its objectives and its importance for decision making processes in organizations. The competitive intelligence cycle stages have been described, as well as the information sources, the information analysistechniques and the information technology tools used in each of the activitys stages. A study involving eleven competitive intelligence professionals has been conducted, with emphasis on information professionals, in order to characterize their performance concerning competitive intelligence cycle stages and also to point out their abilities and skills to perform in each of the cycles phases. It was concluded that information professional participation in competitive intelligence activities is important; said professional performs tasks related to all of the cycles stages, except for the information analysis stage, in which the performance has been less prominent, and that his or her abilities and skills are in accordance with that which the main authors in the literature review advocate.